Planktonic interference and biofilm alliance between aggregation substance and endocarditis- and biofilm-associated pili in Enterococcus faecalis - Afonina, Irina (2018)
Like many bacteria, Enterococcus faecalis encodes a number of adhesins involved in colonization or infection of different niches. Two well-studied E. faecalis adhesins, aggregation substance (AS) and endocarditis- and biofilm-associated pili (Ebp), both contribute to biofilm formation on abiotic surfaces and in endocarditis, suggesting that they may be expressed at the same time. Because different regulatory pathways have been reported for AS and Ebp, here, we examined if they are coexpressed on the same cells and what is the functional impact of coexpression on individual cells and within a population. We found that while Ebp are only expressed on a subset of cells, when Ebp and AS are expressed on the same cells, pili interfere with AS-mediated clumping and impede AS-mediated conjugative plasmid transfer during planktonic growth. However, when the population density increases, horizontal gene transfer rates normalize and are no longer affected by pilus expression. Instead, at higher cell densities during biofilm formation, Ebp and AS differentially contribute to biofilm development and structure, synergizing to promote maximal biofilm formation.